Fostering quality of life in young adults living with multiple sclerosis: a pilot study of a co-created integrated intervention - Poli, Silvia; Donisi, Valeria; Mazzi, Maria Angela; Gobbin, Francesca; Giusto, Giorgia; Orlandi, Riccardo; Schena, Federico; Del Piccolo, Lidia; das Nair, Roshan; Gajofatto, Alberto; Rimondini, Michela (Frontiers in Psychology, 2024)
Introduction. Multiple sclerosis (MS) is generally diagnosed at an early age, making the acceptance of this chronic disease challenging. Research dedicated to young adults with MS (YawMS) is still limited.A biopsychosocial co-created intervention for YawMS integrating social, physical and psychological activities was developed (ESPRIMO intervention) in order to improve the quality of life (QoL) and well-being. This pre-post intervention assessment study examines the feasibility of the ESPRIMO intervention and its signal of efficacy.Method. Inclusion criteria were: age 18-45 years, MS diagnosis, Expanded Disability Status Scale score <3.5. After giving informed consent, YawMS completed a battery of questionnaires which was repeated after the intervention. The battery included a bespoke feasibility scale, the COOP/WONCA charts, and the Short Form-12 Health Survey (SF-12).Results. Fifty-three YAwMS were enrolled and 43 (81.1%) completed the intervention. The majority of the sample positively rated the pleasantness, usefulness and feasibility of the intervention. A significant change in the COOP/WONCA “general QoL” chart (t=3.65;p<0.01) and SF-12 mental wellbeing component (t=-3.17;p<0.01) was found. Discussion. ESPRIMO is an innovative intervention that is feasible; preliminary results show an improvement in QoL and mental wellbeing. Further studies are needed to test its efficacy and evaluate future implementation in health services.The study has been registered at ClinicalTrials.gov (ClinicalTrials.gov ID: NCT04431323).